2019
DOI: 10.1111/bjh.16203
|View full text |Cite
|
Sign up to set email alerts
|

Patients aged less than 3 years with acute myeloid leukaemia characterize a molecularly and clinically distinct subgroup

Abstract: Summary Although infants (age <1 year) with acute myeloid leukaemia (AML) have unique characteristics and are vulnerable to chemotherapy, children aged 1–2 years with AML may have characteristics similar to that of infants. Thus, we analysed 723 paediatric AML patients treated on the Japanese AML99 and AML‐05 trials to identify characteristics of younger children. We identified patients aged <3 years (the younger group) as a distinct subgroup. KMT2A‐rearrangement (KMT2A‐R), CBFA2T3‐GLIS2, CBFB‐MYH11 and NUP98‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…Although the high incidence of MLL‐R in the case of children AML, the relationship between MLL‐R and outcome in AML is less straightforward than in ALL 29 . Hara et al reported that MLL‐R has age‐specific prognostic effect, and the children ≤3 years with this fusion gene had a better prognosis than the older ones 30 . Conversely, when analyzing a large cohort of pediatric AMLs with MLL‐R , 5‐year EFS and OS were poorer, when compared with all pediatric AML 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the high incidence of MLL‐R in the case of children AML, the relationship between MLL‐R and outcome in AML is less straightforward than in ALL 29 . Hara et al reported that MLL‐R has age‐specific prognostic effect, and the children ≤3 years with this fusion gene had a better prognosis than the older ones 30 . Conversely, when analyzing a large cohort of pediatric AMLs with MLL‐R , 5‐year EFS and OS were poorer, when compared with all pediatric AML 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Infant acute myeloid leukemia (AML) has been conventionally defined as AML in patients aged <1 year [1,2,8]. If infant specific features can be seen up to 3 years, they are more prominent up to 2 years of age and many groups agree to define the infant group by children less than 2 years of age [1,9].…”
Section: Agementioning
confidence: 99%
“…The incidence of pediatric AML is estimated to be between 5 and 7 cases per million people per year, with a peak of incidence at 11 cases per million people per year at 2 years of age [10]. Infant AML is a distinct entity, representing 10-25% of pediatric AML, depending on age limits: 32% of children if the cut off is set at 3 years old in a Japanese cohort, 12% of children if <1 or 24% <2 years old in a ELAM02 French cohort [1,2]. Overall AML in children less than 2 years of age represent a fourth of childhood AML with unique features.…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations